Professional Learning: Gaps and Transitions on the Way from Novice to Expert
XXIV, 308 p.
Keywords: About the Book Series The idea for the Book Series “Innovation and Change in Professional Education” (ICPE) was born in 1996. While working on another publication in this area, we noticed that professional educators faced similar problems without even knowing from each other. It was this observation that resulted in examining the possibilities for a new publication platform about professional education with input from different professions. We wanted to develop a publication source that would bring together educators and researchers to exchange ideas and knowledge about theory, research and professional practice. But we were not only striving for a book series informing readers about important themes in the professions. A second goal was to focus on processes of change and innovation. We were heavily involved in innovations going on in our institutions, and were convinced that a better understanding was needed in a wide range of issues critically important to the future of professional education. It was our belief that scholarly publications about innovation processes may support fundamental change in professional education. ICPE reflects our view that professional education deserves such a publication platform. It aims to approach critical questions of educational innovations, and to examine dynamics of educational change in various professional domains in the context of innovation processes. The books will include contributions from frontline practitioners, leading researchers, or distinguished scholars in professional education, delivering reports of empirical or theoretical research, reviews, interpretations of evaluation studies, or descriptions of innovative approaches.